2010
DOI: 10.1159/000314078
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Prostate Cancer Gene 3 in Reference to the Individual Clinical Background: Implications for Daily Practice

Abstract: Introduction: The prostate cancer gene 3 (PCA3) urine assay for the diagnosis of prostate cancer was introduced into clinical practice at the end of 2006. We report our experience with the test in a routine clinical setting and discuss the interpretation of the test results in the context of the individual patient history. Material and Methods: We retrospectively reviewed the data of all patients who received PCA3 determination during a visit to our outpatient clinic between January and June 2008. Prostate vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Setting a PCA3 cut-off at 20 vs 35 would have avoided 22.9% vs 38.1% of biopsies but 3 (9.4%) and 9 cases (28%) of cancer with GS of 6 would have been missed. Despite these interesting reports, PCA3 accuracy (cut-off ≥ 35) at repeated biopsy remains contradictory: sensitivity, specificity, PPV and NPV range between 47 to 76.6% (5), 66.6 to 78.6% (6), 39 to 74% (16) and 62.5 to 87% (17), respectively; in fact, only NPV is satisfactory being > 80% in three of the five studies evaluated (5,6,17,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Setting a PCA3 cut-off at 20 vs 35 would have avoided 22.9% vs 38.1% of biopsies but 3 (9.4%) and 9 cases (28%) of cancer with GS of 6 would have been missed. Despite these interesting reports, PCA3 accuracy (cut-off ≥ 35) at repeated biopsy remains contradictory: sensitivity, specificity, PPV and NPV range between 47 to 76.6% (5), 66.6 to 78.6% (6), 39 to 74% (16) and 62.5 to 87% (17), respectively; in fact, only NPV is satisfactory being > 80% in three of the five studies evaluated (5,6,17,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In daily practice, the PCA3 Assay is increasingly being used [9][10][11][12]. Since thousands of patients are treated each day, aggregated clinical expertise from physicians using the PCA3 Assay in their daily clinical practice may provide additional valuable information to evidence-based information on how this test can be integrated in current initial management of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…PSA), may aid in guiding biopsy decisions and reducing the number of unnecessary biopsies [5][6][7][8]. In daily clinical practice, the PCA3 Assay is increasingly being used for this purpose [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, 12 additional studies included matched results of PCA3 and the comparators but enrolled men with both initial and repeat biopsies or they did not report biopsy history. 10,11,[35][36][37][38][39][40][41][42][43][44] Most often, the results from these studies were not stratified by biopsy history.…”
Section: Clinical Validitymentioning
confidence: 99%
“…Fifteen studies [9][10][11]30,32,[34][35][36][37][38][39][40][41][42][43]46 reported AUC estimates for tPSA and PCA3 in the same population. Overall, 13 [9][10][11]30,32,34,35,37,38,[40][41][42]46 of the15 studies found that the AUC of PCA3 was higher than that of tPSA.…”
Section: Clinical Utilitymentioning
confidence: 99%